Unhealthy fear: Influence of general health on fear of crime. Issue 12 (1st November 2017) - Chadee, Derek; Sooknanan, Grace; Williams, Diana
Abstract: The current study proposed general health as a predictor of fear of crime with risk perception and general fear as mediating factors. Data were collected from a randomly selected household sample using face to face interviews ( n  = 300) and utilizing the following scales: general health, general fear, fear of crime, and perceived risk of victimization. Findings confirm hypothesis that persons with low general health will experience higher fear of crime, a relationship mediated by both general fear and perceived risk of victimization. A significant gender difference was observed with general fear significantly mediating relationship for females, and risk of perceived victimization mediating for males. Implications of findings are discussed in the context of previous and future research.